Sputum cytology for the diagnosis of lung cancer - Comparison of smear and modified cell block methods - (:unkn) unknown (KARGER, 2003)
OBJECTIVE: To compare the sputum smear cytology and cell block methods for specimen adequacy, cytologic quality and diagnostic accuracy in the diagnosis of lung cancer. STUDY DESIGN: We assessed 2,524 sputum specimens from 768 patients. The specimens were prepared as smears and cell blocks for cytopathologic examination between March 1, 1992, and December 31, 1998. The smear and cell block slides were evaluated both separately and together, and the results were compared with radiologic and histopathologic diagnoses. RESULTS: The sensitivity of the smear method was 69.4% and specificity was 99.5%. The sensitivity of the cell block method was 84.4% and specificity, 100%. The sensitivity of the smear and cell block together was 87.6% and specificity, 99.5%. CONCLUSION. The cell block method increases the sensitivity and specificity of sputum cytology, and when smear and cell block slides are evaluated together, sensitivity reaches its highest value. Therefore, application of smear and cell block methods together seems most useful in the diagnosis of lung cancer.
Keywords: lung cancer; sputum; smear; cell block; CARCINOMA; SPECIFICITY; SENSITIVITY